2009
DOI: 10.1111/j.1365-2427.2008.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate hydraulic preferences and predicted impacts of changes in discharge in a large river

Abstract: 1. Instream habitat models are attractive tools for assessing the impacts of flow restoration on aquatic organisms, but have been rarely used for invertebrates due to the lack of knowledge of their hydraulic preferences. 2. In this study, we provide quantitative models of the hydraulic preferences for 66 invertebrate taxa found in the Upper Rhô ne River (France), and combine these preferences with a statistical habitat model (FSTress) to predict the effects of minimum flow restoration on invertebrate abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 58 publications
1
65
0
Order By: Relevance
“…To measure the consequence of the establishment of D. villosus on the potential LBR in the Rhône River, we used data from Mérigoux et al (2009). In these studies, the density of amphipods in the Rhône River was measured at Belley, before the establishment of D. villosus, in Spring and Summer 2002.…”
Section: Rate Of Breakdown Of Dead Leaves By Native and Invasive Speciesmentioning
confidence: 99%
“…To measure the consequence of the establishment of D. villosus on the potential LBR in the Rhône River, we used data from Mérigoux et al (2009). In these studies, the density of amphipods in the Rhône River was measured at Belley, before the establishment of D. villosus, in Spring and Summer 2002.…”
Section: Rate Of Breakdown Of Dead Leaves By Native and Invasive Speciesmentioning
confidence: 99%
“…More specifically, within the family of Limnephilidae, the different species occur along a wide range of flow velocities (Mérigoux and Dolédec 2004;Dolédec et al 2007;Sagnes et al 2008;Mérigoux et al 2009). This difference is also reflected by their drift numbers under different flow conditions (Gibbins et al 2005(Gibbins et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A more complete habitat spectrum could be sampled and other explanatory variables could be tested to enhance model quality. For instance, Mérigoux et al (2009) showed that D. polymorpha and D. tigrina, have pronounced hydraulic preferences in the main channel of the Rhône River. Limitations in the habitat modelling for alien species could also originate in the presence of cryptic species.…”
Section: Ecological Niche Of the Alien Speciesmentioning
confidence: 99%
“…Nevertheless, this sector is located between two potential sources of colonisation: Lake Geneva upstream and the downstream part of the Rhône River, which is connected to the Rhine via the Saône River. Furthermore, after almost two centuries of embankment and hydro-power construction, the Upper-Rhône floodplain is currently being subjected to a hydrological and ecological restoration programme, which started in 2004 (see Mérigoux et al(2009) for details of this restoration programme). As part of this programme, several floodplain channels were deepened or reconnected to the main channel, and forest harvesting and replanting have occurred.…”
Section: Introductionmentioning
confidence: 99%